(3y-1)(2y-3)+(6y+5)(y-4)=?
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 13:28:01
(3y-1)(2y-3)+(6y+5)(y-4)=?(3y-1)(2y-3)+(6y+5)(y-4)=?(3y-1)(2y-3)+(6y+5)(y-4)=?(3y-1)(2y-3)+(6y+5)(y-
(3y-1)(2y-3)+(6y+5)(y-4)=?
(3y-1)(2y-3)+(6y+5)(y-4)=?
(3y-1)(2y-3)+(6y+5)(y-4)=?
(3y-1)(2y-3)+(6y+5)(y-4)
=6y^2-11y+3+6y^2-19y-20
=12y^2-30y-17
y (3y^2+8y-3)-6y(3y+2y-1)+9y
通分 y+3/y*y-6y+9,1/2y+6,y-1/y*y-9
y(y-2)²-y(y+3)(y-5) y=1/2 化简求值
y(y-2)²-y(y+3)(y-5) y=1/2 化简求值
y(y-2)²-y(y+3)(y-5) y=1/2 化简求值
计算:[(y+1)/(y^2-4y+3)减去(y-2)/(y^2-6y+9)]除以(y-5)/(y-1)
解3y+5/3y-6=1/2+5y-4/2y-4
计算(3y-1)(2y+3)-(6y-5)(y-4)
(3y-1)(2y-3)+(6y-5)(y-4)=?xie
(3y-1)(2y一3)十(6y一5)(y一4)
(3y-1)(2y-3)+(6y+5)(y-4)=?
解方程3/y-1+5y-2/y2-y=6/y
[T,Y]=ode45(@rigid,[0 1],[rand(15,1)]);plot(T,Y(:,1),'-',T,Y(:,2),'-.',T,Y(:,3),'.',T,Y(:,4),'-',T,Y(:,5),'-.',T,Y(:,6),'.',T,Y(:,7),'-',T,Y(:,8),'-.',T,Y(:,9),'.',T,Y(:,10),'-',T,Y(:,11),'-.',T,Y(:,12),'-.',T,Y(:,13),'.',T,Y(:,14),'-',T,Y(:,15),'.')
2y+5/3y-6-y/2=5y-4/2y-4
2(y-4)(3y+2)-5(-3y+7)(y+1),其中y=-1
5y∧2-(y-2)(3y+1)-2(y+1)(y-5)
解方程:3y^2-(2y+1)(y-1)=(y-5)(y+1)
解方程3y^2-(2y+1)(y-2)=(y-5)(y-1)